The use of serious games as an innovative educational strategy for learning cardiopulmonary resuscitation: an integrative review - Tainá Vilhar Siqueira; Juliana da Silva Garcia Nascimento; Jordana Luiza Gouvêa de Oliveira; Daniela da Silva Garcia Regino; Maria Celia Barcellos Dalri (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To analyze the scientific evidence available in literature on the use of serious games for health students to learn about cardiopulmonary resuscitation. Methods: Integrative review in PubMed / MEDLINE®, LILACS, Scopus and CINAHL databases. Included primary studies, in Portuguese, English or Spanish, from January 2009 to August 2019. The Rayyan software was used for study selection. Results: We identified 115 studies, and 8 composed the sample, categorizing two domains: : Intention of the study with regard to cardiopulmonary resuscitation through the serious game, and method used by the serious game to teach CPR. Conclusion: Medical students are the main audience for serious game learning, and the main intentions of the games are to compare their effectiveness with traditional methodologies and knowledge retention. The method adopted is the description of a cardiorespiratory arrest for training. The serious game proved effective for learning cardiopulmonary resuscitation.